Chemically modified poly(arylene ether ketone)s with pendant imidazolium groups: Anion exchange membranes for alkaline fuel cells. (1st March 2018) - Tuan, Cao Manh; Patra, Astam K.; Kim, Dukjoon
Abstract: Anion exchange membranes (AEMs) with high stability are prepared for alkaline fuel cells using poly(arylene ether ketone)s (PAEKs) containing pendant imidazolium groups (via a direct step-growth polycondensation reaction). 1 H nuclear magnetic resonance spectroscopy ( 1 H NMR) and Fourier transform infrared (FT-IR) spectroscopy are used to analyze the chemical structure of the prepared PAEK membranes. The anion conductivity, water uptake and swelling ratio, thermal, mechanical, and chemical stability of these membranes are investigated for PAEK membranes with different 1-(3-aminopropyl)imidazole (API) molar ratios (PAEK-API-x) in details. The anion conductivity of PAEK-API-x membranes increases with increasing molar ratio of API. The membrane with API 1.5 equiv. displays the highest anion conductivity (0.0053–0.0531 S cm −1 from 30 °C to 80 °C). All prepared membranes show good chemical and mechanical stability as well as thermal stability up to 250 °C. This high anion conductivity with good thermal, mechanical, and chemical stability of the membrane show potential advantage to meet the demands for AEMs. Graphical abstract: Highlights: PAEK membranes with pendant imidazolium group was synthesized for AEMFC. Membrane properties were significantly affected by the amount of imidazolium group. Some membranes exhibited higher conductivity than commercial ones. All PAEK membranes showed excellent thermal, mechanical, and chemical stability.